Influence of erbium oxide on structural, physical, elastic and luminescence properties of rice husk biosilicate zinc borotellurite glasses for laser application - Halimah, Mohamed Kamari; Asyikin, A. S.; Nazrin, S. N.; Faznny, Mohd Fudzi (Elsevier, 2021)
Nowadays, active search for more efficient and improved glass material to be employed as laser host has been take place in order to have laser with enhanced performance. In this research, erbium oxide doped rice husk biosilicate zinc borotellurite glasses have been fabricated successfully via conventional melt quenching technique. XRD pattern reveals that the prepared glasses are amorphous in nature while FTIR spectra records the presence of Si-O-Si, TeO3, BO4 as well as BO3 vibrational groups in the fabricated glasses. Increasing density from 3.3505 g/cm3 to 4.1852 g/cm3 along with the rigidity of the glass as hinted in the values for elastic moduli from 55.0 GPa to 250.0 GPa is caused by the incorporation of erbium oxide that reduce the amount of non-bridging oxygen in the glass matrix. Three bands that are recorded in PL spectra correspond to the violet, blue and green emission.